DESAIN GANTUNGAN PAKAIAN SUSUN - Andrian Eka Nursetya (Universitas Mercu Buana, 2020)
The clothes hanger is one of the household products which is used as a supporting tool to hang clothes. In general, people use clothes hangers to dry the clothes, hang clothes in a cupboard, or display the clothes in a clothing store. One of the varieties of clothes hanger which is already known is hack clothes hanger. This product has become the designer's interest. The process of designing the hack clothes hanger involves searching for supporting data, analyzing the data, discovering ideas, designing concepts, making a prototype, evaluating and testing products, and determining the materials prior to the production process and finishing the product. The design of the stack clothes hanger consists of 1 hook, which has six spaces to hang the hanger. Each part has 3 hooks space arranged from top to bottom and it is fused by adding several layers as an organizer or additional place to hang complementary clothes, such as veil, scarf, ties, etc. The total of hooks placed at the bottom is 6 layers. Furthermore, there are 6 hanger arms which can be used to hang men's and women's clothes, such as Kebaya, Robe, Shirt, Suit, T-shirt, and various types of pants. PVC solid board was chosen as a material to make the prototype products of stack clothes hanger design.